Miejsce na ziemi: Nowy Jork : O poezji Anny Frajlich .......... 219 - Niesporek, Katarzyna (Tu jestem / zamieszkuję własne życie : studia i szkice o twórczości Anny Frajlich, 2018)
A PLACE ON THE EARTH: NEW YORK ABOUT ANNA FRAJLICH’S POETRYThe aim of this paper is to demonstrate New York as the leitmotif of Anna Frajlich’s poems. The city is presented in her early creations as a strange and untamed space. This attitude changes in time, when the same space is shown as something close and familiar. In the book “By Boat” it is displayed as a harbour which Frajlich finally calls “my city” because it becomes her second homeland and place on earth.